Comparing The Concept of Halal Tourism in Indonesia and Turky Using “ACES Crescenrating Model” - Tutik Sukmalasari Putri (Jurnal Pariwisata Nusantara (JUWITA), 2023)
Abstract Purpose: This study aims to compare the concept of halal tourism (Halal Tourism) between two countries, namely Indonesia and Turkey in terms of the GMTI 2020 assessment criteria, namely Access, Communication, Environment and Service. Method: The research method used is Library Research with descriptive comparative analysis techniques. Results: The research results show. The implications of this research provide an in-depth description of the concept of tourism and become a reference for each country to increase halal tourism in their respective countries. Contribution: This research contributes to GMTI stakeholders and parties to pay more attention to the state of tourism and become a reference for better tourism assessment and management so that these two countries can compete better.